Pemberdayaan Kelompok Tani Rumput Laut dan Peternak Sapi di Kecamatan Suppa Kabupaten Pinrang - Andi Puspa Sari Idris; Subariyanto Subariyanto (Universitas Negeri Makassar, 2019)
The purpose of this study was to train and guide people of Suppa village in Pinrang regency in cultivateEucheuma Cottonii seaweed, processing seaweed waste and making simple biogas. The problem was theparticipants were not understand the process of cultivating the seaweed, processing seaweed waste to become otherproducts, and processing cow manure to become biogas. Method used in this study was training by showingexamples of implementation and mentoring process. The result of this study showed that the farmers of EucheumaCottonii seaweed able to do seaweed cultivation, do marketing and business management properly, and thefisherwomen able to process seaweed waste into processed products in the form of seaweed jelly and cattle farmerscan utilize their cow manure into biogas.